Vaccine-associated reduction in symptom severity among patients with influenza A/H3N2 disease. Issue 51 (16th December 2015) - Deiss, Robert G.; Arnold, John C.; Chen, Wei-Ju; Echols, Sara; Fairchok, Mary P.; Schofield, Christina; Danaher, Patrick J.; McDonough, Erin; Ridoré, Michelande; Mor, Deepika; Burgess, Timothy H.; Millar, Eugene V.
Abstract: Background: The moderate level of protection conferred by influenza vaccines is well-known, but the vaccine's ability to attenuate symptom severity among vaccinated individuals (i.e., vaccine failures) has not been established. Methods: We enrolled otherwise healthy adults who presented with influenza-like illness (ILI) at five US military hospitals between 2009 and 2014. Influenza was diagnosed and subtyped by PCR. Individual and composite severity scores were compared between those who had vs. had not received the seasonal influenza vaccine >14 days prior to enrollment. Results: A total of 155 cases of influenza (A/H1N1, n  = 69; A/H3N2, n  = 66; A/untyped, n  = 3; B, n  = 17) were identified, of whom 111 (72%; A/H1N1, n  = 44; A/H3N2, n  = 52; A/untyped, n  = 3; B, n  = 12) had been vaccinated. Women were significantly less likely to be vaccinated than men (49% vs. 89%; p  < 0.01). In multivariate analysis, vaccinated individuals were significantly less likely to report a fever >101 °F (OR 0.24; 95% CI [0.10, 0.62]) and more likely to report myalgias (OR 3.31; 95% CI [1.22, 8.97]) than vaccinated individuals. Among patients with A/H3N2 infection, upper respiratory and total symptom severity scores were significantly lower for vaccinated patients during the first 2 days of illness, and differences in total symptom severity persisted over 7 days ( p  < 0.05 for all comparisons). Differences across additional symptom categories (lower respiratory and systemic) were also observed throughout 7 days of illness in bivariate analyses. Differences in symptom severity were not observed between vaccinated and unvaccinated participants with A/H1N1 infection. Conclusions: Among patients with A/H3N2 infection, receipt of seasonal influenza vaccine was associated with reduced symptom severity. Patient-centered discussion about the benefits of influenza vaccination should be expanded to include the possibility that the vaccine could attenuate symptoms.